2022
DOI: 10.1007/s11553-021-00930-0
|View full text |Cite
|
Sign up to set email alerts
|

Selbstimage und öffentliches Image des Pflegeberufs: eine quantitative und qualitative Querschnittsstudie

Abstract: Zusammenfassung Hintergrund Ein schlechtes Image der Pflege stellt für den Beruf ein großes Problem dar. Ziel Diese Erhebungen hatten zum Ziel, empirische Daten in Bezug auf das Selbstimage von diplomierten Pflegefachpersonen in der Schweiz am Beispiel des Oberwallis zu erheben und darzulegen, wie diplomierte Pflegefachpersonen in der Schweiz ihr öffentliches Image einschätzen. Das Selbstimage der diplomierten Pflegefachpersonen sollte dann m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…From the society perspective, academic education is not considered necessary. 30 These results are also con rmed by the ndings of Norman, who has demonstrated that other professions, such as medicine, are perceived as very academic, while nurses are classi ed as less intellectual and academic. 31 It has been observed, however, that it is nurses themselves who contribute to such an image.…”
Section: Public Image Of Nurses and Midwivesmentioning
confidence: 52%
See 1 more Smart Citation
“…From the society perspective, academic education is not considered necessary. 30 These results are also con rmed by the ndings of Norman, who has demonstrated that other professions, such as medicine, are perceived as very academic, while nurses are classi ed as less intellectual and academic. 31 It has been observed, however, that it is nurses themselves who contribute to such an image.…”
Section: Public Image Of Nurses and Midwivesmentioning
confidence: 52%
“…1,6 It is assumed that nurses in this country more and more often feel appreciated by the society. 30 The fact than nurses assess the public image with regard to interpersonal strength (factor 1) and interpersonal skills (factor 3) the lowest con rms the claim that nurses are appreciated by their trusting character, but often there is limited public understanding of their professionalism and competencies. 31 In the study group, independence in taking important decisions on the care of patients and in their own work is much more often mentioned by nurses (p= 0.001).…”
Section: Public Image Of Nurses and Midwivesmentioning
confidence: 99%
“…Nurses derive their self-assessment and professional identity from the public image, work environment, work value, education and traditional social and cultural values. In comparison to other studies [ 62 ] participants of this study have assessed a higher public image. It is assumed that nurses in this country feel appreciated by society more and more often.…”
Section: Discussionmentioning
confidence: 97%